2008
DOI: 10.1177/147323000803600608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thiamine Pyrophosphate on Levels of Serum Lactate, Maximum Oxygen Consumption and Heart Rate in Athletes Performing Aerobic Activity

Abstract: The aim of this study was to determine the effect of thiamine pyrophosphate (TPP) on serum lactate levels, maximum oxygen consumption (VO 2max ) and heart rate in male athletes performing aerobic activity. A double-blind, randomized, crossover study was performed in which lactate levels, VO 2max and heart rates in 27 male athletes were compared at rest and after exercise, following administration of placebo (sodium chloride 0.9%) or TPP (1 mg/kg). At rest, serum lactate levels after placebo or TPP were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…This study showed that there was no significant difference in the recovery of heart rate after supplementation with both creatine and thiamine. Previous studies showed creatine and thiamine supplementation both contribute significantly to decreases in heart rate after exercise (Bautista-Hernández, López-Ascencio, Del Toro-Equihua, & Vásquez, 2008;Sanchez-Gonzalez, Wieder, Kim, Vicil, & Figueroa, 2011). However, in the present study, the mean values of heart rate recovery in the creatine group were only slightly lower than the thiamine group with a significance value of p > 0.05.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…This study showed that there was no significant difference in the recovery of heart rate after supplementation with both creatine and thiamine. Previous studies showed creatine and thiamine supplementation both contribute significantly to decreases in heart rate after exercise (Bautista-Hernández, López-Ascencio, Del Toro-Equihua, & Vásquez, 2008;Sanchez-Gonzalez, Wieder, Kim, Vicil, & Figueroa, 2011). However, in the present study, the mean values of heart rate recovery in the creatine group were only slightly lower than the thiamine group with a significance value of p > 0.05.…”
Section: Resultscontrasting
confidence: 90%
“…As for the effect of thiamine supplementation on heart rate recovery, Bautista-Hernández, López-Ascencio, Del Toro-Equihua, & Vásquez (2008) conducted research on 27 athletes. Athletes were given thiamine 1 mg per kg of body weight.…”
Section: Resultsmentioning
confidence: 99%
“…There is scant prior literature on the effect of thiamine on V : O 2 , but in (9). Although there have been no prior studies in critically ill patients, an increase in maximal V : O 2 after administration of thiamine to healthy male athletes has been described (8). Our study is the first to our knowledge to investigate this effect in critically ill patients.…”
Section: Discussionmentioning
confidence: 69%
“…Investigators have shown previously that thiamine deficiency is more common in the critically ill (6,7). Thiamine administration has also been shown to improve V : O 2 and lower lactate in an animal model of sepsis and in healthy humans, regardless of initial thiamine level (8,9). This suggests that thiamine may augment aerobic metabolism in the critically ill, even in the absence of absolute deficiency.…”
mentioning
confidence: 96%
“…An increase in aerobic metabolism should lead to an increase in V o 2 , and our pilot single-arm study supported this hypothesis in showing an increase in V o 2 after thiamine administration in patients with preserved cardiac index (12). That pilot study, as well as one previous randomized trial in healthy adults, suggested that thiamine can augment V o 2 even in the absence of thiamine deficiency or frank impairment in oxygen extraction (10). The lack of a detectable effect in the present study, however, together with the results of the previously described randomized trial in septic shock (13) and three more recent trials of thiamine, ascorbic acid, and corticosteroids (14–16), suggest that thiamine may not function as a universal “metabolic resuscitator” unless there is clear dysfunction of aerobic metabolism and/or clinically significant thiamine deficiency.…”
Section: Discussionmentioning
confidence: 92%